Changing Epidemiology of COVID-19 in Children and Adolescents Over Four Successive Epidemic Waves in South Africa, 2020–2022. Issue 3 (17th January 2023) - Chiwandire, Nicola; Jassat, Waasila; Groome, Michelle; Kufa, Tendesayi; Walaza, Sibongile; Wolter, Nicole; von Gottberg, Anne; Zar, Heather J; Reubenson, Gary; Tempia, Stefano; Ebonwu, Joy; Govender, Nevashan; et al.
Abstract: Background: South Africa experienced four waves of SARS-CoV-2 infection, dominated by Wuhan-Hu, Beta, Delta, and Omicron (BA.1/BA.2). We describe the trends in SARS-CoV-2 testing, cases, admissions, and deaths among children and adolescents in South Africa over successive waves. Methods: We analyzed national SARS-CoV-2 testing, case, and admissions data from March 2020 to February 2022 and estimated cumulative rates by age group for each endpoint. The severity in the third versus the fourth wave was assessed using multivariable logistic regression. Results: Individuals ≤18 years comprised 35% (21, 008, 060/60, 142, 978) of the population but only 12% (424, 394/3, 593, 644) of cases and 6% (26, 176/451, 753) of admissions. Among individuals ≤18 years, infants had the highest admission (505/100, 000) rates. Testing, case, and admission rates generally increased successively in the second (Beta) and third (Delta) waves among all age groups. In the fourth (Omicron BA.1/BA.2) wave, the case rate dropped among individuals ≥1 year but increased among those <1 year. Weekly admission rates for children <1 year (169/100, 000) exceeded rates in adults (124/100, 000) in the fourth wave. The odds of severe COVID-19 in all admitted cases were lower in the fourth wave versus the third wave in each age group, but they were twice as high in admitted cases with at least one comorbidity than those without. Conclusions: The admission rate for children <5 years was higher in the fourth wave than in previous waves, but the overall outcomes were less severe. However, children with at least one comorbidity had increased odds of severe disease, warranting consideration of prioritizing this group for vaccination.